Ophthalmic Biomarkers for Alzheimer’s Disease: A Review - Majeed, Ayesha; Marwick, Ben; Yu, Haoqing; Fadavi, Hassan; Tavakoli, Mitra (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterised by neuronal loss, extracellular amyloid-β (Aβ) plaques, and intracellular neurofibrillary tau tangles. A diagnosis is currently made from the presenting symptoms, and the only definitive diagnosis can be done post-mortem. Over recent years, significant advances have been made in using ocular biomarkers to diagnose various neurodegenerative diseases, including AD. As the eye is an extension of the central nervous system, reviewing changes in the eye’s biology could lead to developing a series of non-invasive, differential diagnostic tests for AD that could be further applied to other diseases. Significant changes have been identified in the retinal nerve fibre layer, cornea, ocular vasculature, and retina. In the present paper, we review current research and assess some ocular biomarkers' accuracy and reliability that could potentially be used for diagnostic purposes. Additionally, we review the various imaging techniques used in the measurement of these biomarkers.